AltitudeOmics: Resetting of Cerebrovascular CO2 Reactivity Following Acclimatization to High Altitude - Fan, Jui-Lin; Subudhi, Andrew W.; Duffin, James; Lovering, Andrew T.; Roach, Robert C.; Kayser, Bengt (Frontiers in Physiology, 2016)
Previous studies reported enhanced cerebrovascular CO2 reactivity upon ascent to high altitude using linear models. However, there is evidence that this response may be sigmoidal in nature. Moreover, it was speculated that these changes at high altitude are mediated by alterations in acid-base buffering. Accordingly, we reanalyzed previously published data to assess middle cerebral blood flow velocity (MCAv) responses to modified rebreathing at sea level (SL), upon ascent (ALT1) and following 16 days of acclimatization (ALT16) to 5,260 m in 21 lowlanders. Using sigmoid curve fitting of the MCAv responses to CO2, we found the amplitude (95% vs. 129%, SL vs. ALT1, 95% confidence intervals (CI) [77, 112], [111, 145], respectively, P=0.024) and the slope of the sigmoid response (4.5 vs. 7.5 %/mmHg, SL vs. ALT1, 95% CIs [3.1, 5.9], [6.0, 9.0], respectively, P=0.026) to be enhanced at ALT1, which persisted with acclimatization at ALT16 (amplitude: 177%, 95% CI [139, 215], P<0.001; slope: 10.3 %/mmHg, 95% CI [8.2, 12.5], P=0.003) compared to SL. Meanwhile, the sigmoidal response midpoint was unchanged at ALT1 (SL: 36.5 mmHg; ALT1: 35.4 mmHg, 95% CIs [34.0, 39.0], [33.1, 37.7], respectively, P=0.982), while it was reduced by ~7 mmHg at ALT16 (28.6 mmHg, 95% CI [26.4, 30.8], P=0.001 vs. SL), indicating leftward shift of the cerebrovascular CO2 response to a lower arterial partial pressure of CO2 (PaCO2) following acclimatization to altitude. Sigmoid fitting revealed a leftward shift in the midpoint of the cerebrovascular response curve which could not be observed with linear fitting. These findings demonstrate that there is resetting of the cerebrovascular CO2 reactivity operating point to a lower PaCO2 following acclimatization to high altitude. This cerebrovascular resetting is likely the result of an altered acid-base buffer status resulting from prolonged exposure to the severe hypocapnia associated with ventilatory acclimatization to high altitude.